Capitalism in the Platform Age Emerging Assemblages of Labour and Welfare in Urban Spaces - Mezzadra, Sandro; Cuppini, Niccoló; Frapporti, Mattia; Pirone, Maurilio (Springer Studies in Alternative Economics, 2024)
This open access book provides an overview of urban digital platforms such as Airbnb and Deliveroo, which, along with Amazon, Google, Facebook and other IT companies, constitute by now the infrastructures for other businesses to operate on and for our social life to go on. These platforms serve as standards-based techno-economic systems that simultaneously capture cooperation through remote coordination and organize labor via algorithm management. Based on a three-years research project, this contributed volume outlines a general theory of platform capitalism that conceives these platforms not only as technical devices, but as generative engines that operate at the interface of several aspects, such as digitalization of forms of social cooperation; algorithm-based management of labor and participation; and private and vertical appropriation of profits. These elements are somehow iconic of the capitalist evolution of the last decades, and they open up a reflection on new forms of "primitive accumulation" (in particular regarding data), on the mechanisms used to capture and extract social surplus value, and on the logistic-financial dimensions of capital. Finally, in light of the transformations associated with the COVID-19 pandemic, the authors examine how platforms can evolve into hegemonic organizational structures. Assuming we are all already living in the age of the platform, this book takes a multifaceted approach-combining sociology with urban studies, and political sciences with economics-to grasp the challenges our societies face in terms of ensuring fair economic growth, adequate social protections, and labor rights. It will appeal to anyone interested in digital platforms and how they are changing the organization of labor, urban spaces, and forms of governance.